Probing 8th Grade Students’ Conception about Heat and Temperature Using Three-Tier Test : A Case Study - Setyaningrum, V; Sopandi, W (Jurnal Pendidikan Fisika Indonesia, 2021)
The aim of this study is to investigate the various categories of students' conceptions about heat and temperature, so that the misconceptions that students may have can be prevented and regenerated as early as possible.The subjects of this study were 203 8th grader students in one of the Junior High Schools in Mempawah District, West Kalimantan. Data was collected using a three-tier test developed by Kusumah (2013), questionnaire and interview.The data were analyzed and categorized based on their configuration of the answer, the reasons and confident rating index. Result showed that there are four main categories of students’ conceptions:understand the concepts;lack of knowledge; misconceptions; and error. In addition, students also still have 18 kinds of misconceptions about the heat and the temperature despite the material was studied in their 7th grade. Therefore the results of this study can be used as a basis for teachers so that learning process does not only focus on delivering material, but also improves students’ conceptions.